27‐hydroxycholesterol promotes Aβ accumulation via altering Aβ metabolism in mild cognitive impairment patients and APP/PS1 mice. (22nd January 2019) - Zhang, Xiaona; Xi, Yuandi; Yu, Huiyan; An, Yu; Wang, Ying; Tao, Lingwei; Wang, Yushan; Liu, Wen; Wang, Tao; Xiao, Rong
Abstract: The oxysterol 27‐hydroxycholesterol (27‐OHC) has been considered to play a key role in the pathogenesis of Alzheimer's disease (AD). Because β‐amyloid peptide (Aβ) is the pathological hallmark of AD, the aim of this study is to verify whether 27‐OHC could lead to cognitive impairment through modulating Aβ accumulation and deposition. Regulation of Aβ metabolism was explored as the pathogenic mechanism of 27‐OHC. Furthermore, microRNAs (miRNAs) and their relations with 27‐OHC were also detected. In present study, matched case‐control study and APP/PS1 transgenic mice research were conducted. The results showed that the 27‐OHC and Aβ in plasma were increased in mild cognitive impairment patients, and a slight correlation was found between 27‐OHC and Aβ1‐40. This relationship was also proved by the research of APP/PS1 mice. More severe learning and memory impairment and higher Aβ1‐40 expression in brain and plasma were detected in the APP/PS1 mice of 27‐OHC treatment group. In addition, increased amyloid plaques were also found in the hippocampus of 27‐OHC‐treated mice. In order to find out the mechanism of 27‐OHC on regulating Aβ metabolism, the factors of Aβ production (APP, BACE1 and ADAM10), transport (LRP1 and RAGE) and elimination (NEP and IDE) were tested respectively. The gene and protein expressions of APP, BACE1 and RAGE were increased while LRP1 and IDE were decreased in the brain of 27‐OHC‐treated mice. At last, down‐regulated expression of miRNA let‐7g‐5p was found after 27‐OHC treatment. In conclusion, these findings suggested that excessive 27‐OHC could enhance the accumulation and deposition of Aβ both in brain and blood, resulting in a severe impairment of cognition, especially in the modulation of Aβ1‐40. The mechanism might be associated with the regulation of Aβ metabolism, and miRNA let‐7g‐5p was likely to play a vital role in this pathological process induced by 27‐OHC.